Bydgoszcz na otarcie łez. Polscy uchodźcy z ziem wschodnich w 1920 r. (Kronika Bydgoska, 2021)
In the summer of 1920, when situation started to complicate on the fronts of the Polish-Soviet War, the government decided that the Poles from the eastern lands would be deported to Pomerania and Wielkopolska, including Bydgoszcz. The Committee for Refugee Affairs was established here just like in many other towns. Poles evacuated to Bydgoszcz were coming from Minsk, Slutsk, and the Kiev area. Among them, there were many landowners with years of experience in social and political activities, including Amelia and Włodzimierz Nitosławski from the Vitebsk area and the Lipkowski family from the Uman area. Deportees comprised clerks, lawyers, teachers, and physicians. The latter ones arrived from Kiev. Students attending schools in Babruysk, Minsk, Nyasvizh, Slutsk, and Vawkavysk were also evacuated to Bydgoszcz. With them in mind, the Grammar School for Boys for the Exiles from the Eastern Borderlands was founded. The Kresowy Dormitory for boys was opened in Bydgoszcz and for girls in Chełmno. On the initiative of the exiles in Bydgoszcz, the Union of Poles from the Eastern Borderlands was established. This organization was helping the elderly, sick, and vulnerable, as well as young people attending schools. Many exiles had never returned to their homeland, since based on the Treaty of Riga their native land was no longer part of Poland. Some of the exiles included Edward Woyniłłowicz, Chairman of the Minsk Agricultural Society, the owner of Savichi and Puzovo in Slutsk County. The Poles from the Eastern Borderlands comprised a big community in Bydgoszcz, which had a significant impact on social and cultural activities in the city. They laid down a path to throngs of refugees who arrived to the areas after the end of World War II, when more lands disappeared from the map of Poland.